Criação de um índice de abrangência em reprodução humana assistida - Maria Lectícia Firpe Penna (2015)
Introduction: There is a variety of regulations among the countries regarding the use of assisted reproductive technologies (ART). Objectives: compare the available Brazilian ART regulations with that of other countries and also with their Human Development Index (HDI); creating an index of the insertion of comprehensiveness of ART regulations in Brazil and other countries; compare the insertion of comprehensiveness index with the HDI of different countries. Methodology: quantitative, transversal and descriptive study that compares Brazilian ART rules with 23 other nations. Countries from all continents and different HDI values (all above 0.5) have been reviewed. The data search was made on BVS, PubMed and official sites (Congress, Ministries) from the government and Medical Entities of the studied countries. Articles from Red Latinoamericana de Reproducción Asistida (REDLARA) and the European Society of Human Reproduction and Embryology (ESHRE) were also used. A Human Reproduction Comprehensiveness Index (HRCI) was created to set a quantum to rank nations regarding the permission or inclusion of ART avaible to society. Twenty-one parameters and the indexes they present were investigated considering what can and what cannot be done in each country. The purpose of this measurement is to determine the degree of permissivity of the countries in the use of ART procedures. Results: four countries among 24 were excluded: South Africa don´t have data avaible in literature; and Australia, Canada and USA by presenting different rules for each state, province or region, not allowing analysis of the country as a whole. Considering the HRCI, it was noted that there are eight countries with broader formal or informal ART regulations, more suited to social expectations and 12 with rigid limits and restrictions in the formal or informal rules. It was found no relationship between HDI and the permissivity in the use of ART since the three highest HRCI values were of Israel, India (the lowest HDI among studied countries) and United Kingdom. The three lowest ones were from Peru, Italy and Germany (third largest HDI among studied countries). The differences can be explained due to the way regulations were made and the story of the Assisted Reproduction in each nation. Conclusions: the ART regulations in the studied countries are conducted by professional entities or government legislation. No relationship was found between the HDI and the permissivity to ART procedures in the studied countries. The HRCI originated in this thesis shows objectively how are nations behaving towards the assisted reproduction improvements and their technologies.